Single-cell transcriptional analysis of malaria-specific t lymphocytes following vaccination and protection in humans - Sierra-Davidson, K (2016)
Vaccine approaches that confer durable and high-level protection against malaria infection are urgently needed. Development of next-generation vaccines is partially hindered by a limited understanding of the mechanisms underlying protective immunity. In-depth characterization of such responses will be critical in identifying immune correlates and ultimately guiding the development of next-generation vaccine strategies. The aim of this thesis was to dramatically enhance the breadth and depth of phenotypic analysis from cellular immune responses induced by two malaria vaccine candidates that have demonstrated high-level protection against CHMI: the PfSPZ Vaccine and ChAd63/MVA ME-TRAP. Single cell gene expression analysis of antigen-specific CD4+ and CD8+ T lymphocytes following vaccination and/or CHMI revealed a number of important findings. First, PfSPZ-specific CD4+ T cells from vaccinated and protected subjects in a small cohort were enriched in IL21 gene expression compared to unprotected subjects prior to challenge. Average IL21 expression per-subject correlated with antibody responses against the immunodominant CS protein. Analysis of a larger independent cohort confirmed both of these findings and provided greater power to dissect this population of IL21+ CD4+ T cells. Interestingly, these data provided evidence for a class of Th1/TFH-like cells that could potentially provide help for both CD8+ T cells and humoral responses elicited by PfSPZ vaccination. Second, analysis of CD8+ T cells from subjects vaccinated with ChAd63/MVA ME-TRAP provided the opportunity to investigate cellular immune responses that are critical for clearance of infected hepatocytes. There was evidence for multifunctional use of effector molecules in TRAP-specific CD107a+CD8+ T cells and a broad transcriptional signature of monofunctional IFNG+ CD8+ T cells, which have been previously correlated with protection induced by viral vectors. Overall, data presented in this thesis demonstrate that single-cell transcriptional analysis is a powerful tool to expand the characterization of cellular immune responses and elucidate potential correlates of protection in Phase II clinical trials.